Gestión y captación de ingresos en el programa de incentivos para la mejora de la gestión municipal en la Municipalidad Provincial de Maynas. Periodo 2014-2018 - Valles Alvarado, Walquer (2021)
In 2009, the Incentive Program for the Improvement of Municipal Management was created, which corresponds to an instrument of the Budget for Results. It seeks to improve the quality of public services provided by municipalities at the national level within the framework of results-based management. To do this, it provides incentives for meeting goals and additional bonuses for meeting all of the objectives. However, all the expected results at the municipal level have not yet been reached. Between the years 2014 to 2018, the percentage of compliance with the goals does not reach one hundred percent. One of the municipalities that has not achieved this goal and therefore did not obtain additional bonuses is the Provincial Municipality of Maynas. Faced with this problem, the present study arises, in order to describe the main factors of municipal management that limit the fulfillment of goals and the capture of income through the Incentive Program, in the case of the Provincial Municipality of Maynas during the period 2014-2018. The research presents a mixed methods, of the descriptive type and non-experimental design, of transversal cut. The result is that between 2014 and 2018, the Provincial Municipality of Maynas lost significant amounts in terms of the unearned allocations and the additional bonuses not obtained during the study period. It is also observed among the program management dimensions that planning and coordination are the dimensions that present the least compliance and the greatest shortcomings. Therefore, there are fundamental aspects to work within the management of the Incentive Program in this municipality and the opportunity for improvement in the coming periods.